Representation and judgment : Brentano and Stoicism in Counterpoint - Guerrero Cordero, Felipe Iván (Analysis. Journal of Philosophical Research, 2024)
This paper aims to consider the Stoic roots in Brentano's theory of judgment. It is not, however, intended as a work of philology, that is, it does not seek to teach, source after source, that Brentano's philosophy is elaborated as an interpretation of Stoicism. It will show, instead, that there are thematic affinities between these two great traditions. For this purpose, we will devote three moments. In the first, we will review the notions of phantasy (phantasía) and assent (synkatathésis), as well as cognitive phantasy (phantasía kataleptiké). We will then present the Brentanian theory of judgment, emphasizing the notions of representation (Vorstellung) and judgment (Urteil). Finally, we will try to show thematic similarities in the treatment and interpret inner perception (innere Wahrnehmung) as a paradigmatic case of cognitive phantasy.